THE USE OF ICT AT SECONDARY SCHOOLS THROUGH THE EYES OF STUDENTS - GERHATOVA, Zaneta (Trends in education, 2013)
The 21st century has brought a great expansion of use of information and communication technologies, which find application in various areas of life. In education are very important means of its modernization. In this paper we part of the graphically evaluated results of the survey concerning the use of information and communication technology in secondary schools. The research we realized in the academic year 2011/2012 on a sample of 131 students in the Slovak Republic.
Keywords: information and communication technologies; interactive whiteboard; questionnaire